Remembering the Achaemenids in the Character of Nehemiah: Ancient Jewish Memories of Achaemenid Persia 3 - Fulton, Deirdre N. (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2025)
The portrayal of Nehemiah’s relationship with the Achaemenid Empire shifts significantly across four key Second Temple period texts: Nehemiah, 1 Esdras, 2 Maccabees, and Sirach. In the book of Nehemiah, the Achaemenid king Artaxerxes is depicted as a central and supportive figure, empowering Nehemiah’s efforts to rebuild Jerusalem. Later texts, however, present this relationship in more restrained or ambiguous terms. These variations mark a broader transformation in how Jewish authors of the Hellenistic period remembered and represented foreign imperial authority. As Nehemiah’s connection to the Achaemenids becomes increasingly subdued, his role in the restoration of Jerusalem also undergoes redefinition. A comparative reading of these texts reveals a dynamic memory of Achaemenid rule, shaped by changing historical and cultural contexts.